An annotated checklist of the fig wasps (Hymenoptera: Chalcidoidea) of India. (2nd April 2016) - Pramanik, Achintya; Dey, Debjani
Abstract: A checklist of 115 fig wasp species (Hymenoptera: Chalcidoidea) recorded within the present political boundary of India till 2015 is provided along with a fig–fig wasp host catalogue. Fig wasp taxa have been arranged according to the current classification among 4 families, 6 subfamilies and 33 genera. For each species, correct nomenclature followed by all relevant works reporting systematics and ecology of Indian fig wasps have been provided along with synonyms, host records and distribution within India. Seventy six new distribution records were established for different fig wasps within India along with first report of Ormyrus benjaminae Narendran, 1999 from India. Two new synonyms are proposed, viz., Parapilkhanivora nigra Farooqi & Menon, 1973 syn. nov. for Parasycobia kaurae Abdurahiman & Joseph, 1967 and Parapilkhanivora testacea Farooqi & Menon, 1973 syn. nov. for Sycobiomorphella lacorensis Abdurahiman & Joseph, 1967.